2018
DOI: 10.1007/s13346-018-0519-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemico-calorimetric analysis of amorphous granules manufactured via continuous granulation process

Abstract: The current study explores the first case of the implementation of solution calorimetry (SolCal) in order to determine the amorphous content of crystalline benzoyl-methoxy-methylindol-acetic acid (BMA)-a model poorly soluble drug, in the amorphous granules prepared via single-step continuous twin-screw dry granulations (TSG). Amorphous magnesium aluminometasilicate (Neusilin®) (US2) was used as a novel inorganic carrier via a TwinLab 10 mm twin-screw extruder. The BMA/US2 blends were processed at 180 °C and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These granules demonstrated excellent flow properties, stabilized the drug in its amorphous form, and also demonstrated immediate dissolution in comparison to the crystalline drug. Indomethacin solid dispersions with inorganic excipients such as mesoporous silica have been manufactured previously using solvent evaporation techniques such as rotary evaporation, spray drying, and vacuum drying [55][56][57] where hydroxypropyl methylcellulose (HPMC) and Kollicoat® IR were used as precipitation inhibitors (PIs) combined with mesoporous silica nanoparticles (MSNs) as carriers. The present study manufactured granules with multiple mesoporous inorganic excipients, using a solvent-free, continuous process with in-line monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…These granules demonstrated excellent flow properties, stabilized the drug in its amorphous form, and also demonstrated immediate dissolution in comparison to the crystalline drug. Indomethacin solid dispersions with inorganic excipients such as mesoporous silica have been manufactured previously using solvent evaporation techniques such as rotary evaporation, spray drying, and vacuum drying [55][56][57] where hydroxypropyl methylcellulose (HPMC) and Kollicoat® IR were used as precipitation inhibitors (PIs) combined with mesoporous silica nanoparticles (MSNs) as carriers. The present study manufactured granules with multiple mesoporous inorganic excipients, using a solvent-free, continuous process with in-line monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the transitions observed in melt granulation trials, it can be concluded that twin-screw dry granulation is an effective and relatively safe process to produce quality products. Majumder et al [68] demonstrated Neusilin ® US2 as an alternative carrier in development of amorphous granules with enhanced dissolution for the model drug benzoyl-methoxy-methylindol-acetic acid (BMA) by means of a continuous dry granulation approach.…”
Section: Twin-screw Dry Granulation-dry Granulation Techniques Offer Additionalmentioning
confidence: 99%